OPTIMALISASI MEDIA PEMBELAJARAN BERBASIS AI UNTUK GURU SD NEGERI 1 KARANGANOM KLATEN - Prasetiyo, Hendro Joko; Suradi, Agustinus; Windarti, Mariana (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2024)
Community Service Activities in the form of Training on Learning Media Development Using Artificial Intelligence (AI) Based with Canva Software which will later be used to create Powerpoint, at SD 1 Negeri Karanganom, Klaten Regency aims to provide knowledge and technology regarding the use of the Canva application which will later be used for the learning process for teachers in making Powerpoint so that the appearance will be more interesting and interactive. The training participants are productive teachers who teach at SD 1 Negeri Karanganom, Klaten Regency. This training activity begins with coordinating the PPM TEAM, registering participants and disseminating material. The socialization of the material begins with an introduction and installation of Canva software which will later be integrated to create Powerpoint material for creating learning media. Material socialization was carried out through lectures and discussions as well as practicums in creating PowerPoint learning media using the Canva application. With this program, teachers can easily design and arrange their own to make the learning process using Canva media, especially PowerPoint, more interesting for students because it is not boring. The indicators for achieving targets and outcomes for SD Negeri 1 Karanganom Klaten teachers through Optimizing AI-Based Learning Media using Canva learning media are to improve the quality of teachers in creating AI-based learning media, especially using Canva learning media, being able to develop and create learning aids by making PowerPoint presentations so that the appearance will be more attractive, the effect of which will be to make it easier for students to understand the learning material better.